Primes of the form n2-2. - Canuto, Azleya Trish (Iloilo City UPHSI, 2015)
This paper presented the concept of primes with the form P = n^2 - 2 and determined its properties. It found the following characteristics of P: (a) P is congruent to 3, 7 or 9 modulo 10; (b) any P =/ 7 will never have a twin prime; P > 2 are congruent to 3 modulo 4; and (d) P > 2 are congruent to 7 modulo 8. It also found the following characteristics of n: (a) n > 2 are odd; (b) n =/ 3 is not congruent to +/- 3 modulo 7; and (c) n is not congruent to +/- 6 modulo 17. Lastly, it found that the prime factor p of a non-prime n^2 - 2 is congruent to +/-1 modulo 8.
Research II : Research Manuscripts
Keywords: Primes